SEGMENTATION AND POSITIONING STRATEGY AT SDIT ROBBANI BANJARBARU - Siti Muzalifah; Muhammad Taqiyyuddin (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2023)
This study discusses the segmentation and positioning of educational services at SDIT Robbani Banjarbaru with the aim of knowing the implementation of the segmentation and positioning of Islamic education institutions. This research is a qualitative research with the main target of all school members who are involved in the marketing process. data collection using interview method. The results of this study indicate that: (1) SDIT Robbani Banjarbaru determines market segmentation by applying several segmentation approaches, namely: (a) demographic segmentation; (b) geographic segmentation; (c) psychographic segmentation; and (d) psychological segmentation. (2) SDIT Robbani Banjarbaru determines the positioning of its educational services in the academic and non-academic fields as well as by developing a "child-friendly and brain-friendly" brand. Market segmentation is the first thing that must be done by schools to achieve optimal marketing results, followed by positioning. The position or image formed by the school has a dominant role in influencing public attitudes towards schools.